CNNA Cisco certified network associate review guide - Lammle, Todd.; ebrary, Inc. (Indianapolis : Wiley Technology Pub., 2011)
"Organized by exam objectives, this is a focused, concise review guide that works hand-in-hand with any learning tool, including the Sybex CCNA: Cisco Certified Network Associate Study Guide, 7th and Deluxe editions.The book will consist of eight high-level chapters, each mapping to the eight main Domains of the exam objectives. The book will drill down into the specifics of the exam, covering the following: Describe how a network works Configure, verify and troubleshoot a switch with VLANs and interswitch communications Implement an IP addressing scheme and IP Services to meet network requirements in a medium-size Enterprise branch office network Configure, verify, and troubleshoot basic router operation and routing on Cisco devices Explain and select the appropriate administrative tasks required for a WLAN Identify security threats to a network and describe general methods to mitigate those threats Implement, verify, and troubleshoot NAT and ACLs in a medium-size Enterprise branch office network Implement and verify WAN links The book will also include an interactive CD, with two bonus exams, handy flashcard questions, and a searchable PDF of a Glossary of Terms"--
Includes index.
Electronic reproduction.
Keywords: Computer networks -- Examinations -- Study guides; Telecommunications engineers -- Certification; Electronic books